2019
DOI: 10.1177/0036850419886448
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone enhances the apoptotic effect of 5-fluorouracil in colorectal cancer cells with high-glucose-induced glutathione

Abstract: Colorectal cancer is one of the most prevalent noncommunicable diseases worldwide. 5-Fluorouracil is the mainstay of chemotherapy for colorectal cancer. Previously, we have demonstrated that high glucose diminishes the cytotoxicity of 5-fluorouracil by promoting cell cycle progression. The synergistic impact of rosiglitazone on 5-fluorouracil-induced apoptosis was further investigated in this study. Besides control cell lines (CCD-18Co), two human colonic carcinoma cell lines (HCT 116 and HT 29) were exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…In turn, Lau et al demonstrated the synergistic impact of rosiglitazone on 5-fluorouracil-induced apoptosis of two colorectal cancer cell lines (HCT-116, HT-29). The effect of this combination was significantly stronger compared to 5-FU in monotherapy [178]. Another, PPARγ agonist, trioglitazone significantly suppressed the growth of human oral squamous cell carcinoma cell lines (HSC-4, Ca9-22) by inducing cell cycle arrest [179].…”
Section: Carcinogenesis Modulators: From Basic Research To Clinical Pmentioning
confidence: 96%
“…In turn, Lau et al demonstrated the synergistic impact of rosiglitazone on 5-fluorouracil-induced apoptosis of two colorectal cancer cell lines (HCT-116, HT-29). The effect of this combination was significantly stronger compared to 5-FU in monotherapy [178]. Another, PPARγ agonist, trioglitazone significantly suppressed the growth of human oral squamous cell carcinoma cell lines (HSC-4, Ca9-22) by inducing cell cycle arrest [179].…”
Section: Carcinogenesis Modulators: From Basic Research To Clinical Pmentioning
confidence: 96%
“…UCP2 induction also significantly improved the response to anti-PD1 immunotherapy, and a greater reduction in tumor volume in melanoma xenografts was reported when anti-PD1 was combined with rosiglitazone [ 117 ]. Rosiglitazone also improved radiosensitivity and response to 5-fluorouracil chemotherapy by inhibiting cell growth and suppressing pancreatic and colorectal cancer cells in vitro [ 177 , 178 ].…”
Section: Ucp2 and Cancermentioning
confidence: 99%
“…9 In colorectal cancer, HG induces chemoresistance to 5-fluorouracil by diminishing its cytotoxic effect. 10 Recent research has demonstrated that in diabetic retinopathy, a serious T2D complication, HG inhibits autophagy and diminishes the suppressed capacity of autophagy through the autophagy lysosome pathway. 11 Autophagy is a stress response responsible for clearing aggregated cytosolic proteins, damaged organelles, and invading microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…As AMP‐activated protein kinase (AMPK) acts as an energy sensor that maintains cellular metabolic homeostasis, it has attracted increased attention in various diseases, especially malignant ones 9 . In colorectal cancer, HG induces chemoresistance to 5‐fluorouracil by diminishing its cytotoxic effect 10 . Recent research has demonstrated that in diabetic retinopathy, a serious T2D complication, HG inhibits autophagy and diminishes the suppressed capacity of autophagy through the autophagy lysosome pathway 11 …”
Section: Introductionmentioning
confidence: 99%